Struktur Lirik Nyanyian Indang di Nagari Kuranji Hulu Kecamatan Sungai Geringging Kabupaten Padang Pariaman - Vortixa, Ondia; Agustina, Agustina; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study were to (1) describe song spiritual structures indang at Nagari Kuranji Hulu describe song spiritual structures indang at Nagari Kuranji Hulu Sungai Geringging Kabupaten Padang Pariaman and (2 ) describe song physical structures indang at Nagari Kuranji Hulu Sungai Geringging Kabupaten Padang Pariaman. This observational type is observational kualitatif by methodics descriptive. Descriptive method to be utilized to describe song lyric structure indang at Nagari Kuranji Hulu Sungai Geringging Kabupaten Padang Pariaman. Observational data collecting tech utilize recording tech to get song lyric indang . Besides recording tech also utilizes tech to note to describe of recording language goes to language to write. Base observational result get as follows been concluded.Â  First , Spiritual structure. Spiritual structure that exists in song lyric indang at Nagari Kuranji Hulu Sungai Geringging Kabupaten Padang Pariaman, which is theme, feel (feeling ), tone, and mandate.Â  Both of, physical structure. Physical structure that is revealed in song lyric indang at Nagari Kuranji Hulu Sungai Geringging Kabupaten Padang Pariaman, which is diction, imagination, say konkret, and figuratif's language.